2014
DOI: 10.1073/pnas.1407139111
|View full text |Cite
|
Sign up to set email alerts
|

Role of Erbin in ErbB2-dependent breast tumor growth

Abstract: ErbB2 (v-erb-b2 avian erythroblastic leukemia viral oncogene homolog 2), a receptor tyrosine kinase of the ErbB family, is overexpressed in around 25% of breast cancers. In addition to forming a heterodimer with other ErbB receptors in response to ligand stimulation, ErbB2 can be activated in a ligand-independent manner. We report here that Erbin, an ErbB2-interacting protein that was thought to act as an antitumor factor, is specifically expressed in mammary luminal epithelial cells and facilitates ErbB2-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 52 publications
2
47
0
1
Order By: Relevance
“…Erbin dysregulation has previously been reported in cervical tumors, colon carcinomas and breast carcinomas [12,13,20]. Here, we provide evidence to support the mechanistic connection between Erbin loss and aberrant Skp2-p27 axis, which coordinately drives cancer cells to uncontrolledly proliferate through cell cycle regulation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Erbin dysregulation has previously been reported in cervical tumors, colon carcinomas and breast carcinomas [12,13,20]. Here, we provide evidence to support the mechanistic connection between Erbin loss and aberrant Skp2-p27 axis, which coordinately drives cancer cells to uncontrolledly proliferate through cell cycle regulation.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study form our group demonstrated that Erbin is significantly decreased or lost in cervical cancer tissues and loss of Erbin endows cervical cancer with resistance to anoikis by inhibiting STAT3 signaling [12]. Of note is that other group recently found that Erbin plays a positive role in ErbB2-dependent breast tumor growth [13]. In this regard, the role of Erbin in human cancer is conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical (IHC) staining was performed as described previously(27). Tissue sections were incubated in 10 mM sodium citrate buffer (pH 6.0) at sub-boiling temperatures for 10 min, rinsed in PBS, and incubated with 10% normal goat serum to block non-specific staining.…”
Section: Methodsmentioning
confidence: 99%
“…We recently identified male‐biased genes in the telencephalon of the Bengalese finch, including a Z chromosome gene erbin (ErbB2 interacting protein) and ErbB2 (a homolog of the avian erythroblastic leukemia viral oncogene homolog 2) (Sun et al, ). Both Erbin and ErbB2 have been reported to be involved in cell proliferation, survival, and differentiation through signaling pathways mediated by Erbin (mitogen‐activated protein kinases, MAPK; transforming growth factor β, TGF‐β; nuclear factor‐κB, NF‐κB) or by Erbb2 (extracellular regulated protein kinases, ERK or Ras‐Raf‐Mek‐Erk; protein kinase C, PKC) (Borg et al, ; Rangwala et al, ; Citri and Yarden, ; Zhou et al, ; Roskoski, ; Tao et al, ). Given the reported roles of erbin and erbb2 , we further wanted to know: (1) whether erbin and erbb2 expressions have sexual differences in the developing HVC, a song control nucleus in the Bengalese finch; (2) whether cell proliferation, and neuronal differentiation are affected after injections of erbin‐ or erbb2‐ interfering lentiviruses into the developing HVC and its overlying VZ (after erbin‐ or erbb2 knock‐down).…”
Section: Introductionmentioning
confidence: 99%
“…We recently identified male-biased genes in the telencephalon of the Bengalese finch, including a Z chromosome gene erbin (ErbB2 interacting protein) and ErbB2 (a homolog of the avian erythroblastic leukemia viral oncogene homolog 2) (Sun et al, 2010). Both Erbin and ErbB2 have been reported to be involved in cell proliferation, survival, and differentiation through signaling pathways mediated by Erbin (mitogen-activated protein kinases, MAPK; transforming growth factor b, TGF-b; nuclear factor-jB, NF-jB) or by Erbb2 (extracellular regulated protein kinases, ERK or Ras-Raf-Mek-Erk; protein kinase C, PKC) (Borg et al, 2000;Rangwala et al, 2005;Citri and Yarden, 2006;Zhou et al, 2012;Roskoski, 2014;Tao et al, 2014). Given the reported roles of erbin and erbb2, we further wanted to know:…”
Section: Introductionmentioning
confidence: 99%